(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article explores the pivotal role of entrepreneurship in advancing the standard of living in Uzbekistan. Drawing upon a comprehensive review of international literature and specific contextual factors, the analysis provides insights into the transformative potential of entrepreneurship for economic development, job creation, and innovation. From social reforms to investments in infrastructure, education, and innovation, the article offers actionable insights for policymakers, business leaders, and stakeholders seeking to promote entrepreneurship as a driver of socio-economic progress in Uzbekistan.